Evolution of an Innovative Approach to the Delivery of In‐Person Training in the Responsible Conduct of Research. Issue 6 (20th May 2014) - Schmidt, Karen L.; Yasko, Laurel; Green, Michael; Alexander, Jane; Ryan, Christopher
Abstract The responsible conduct of research (RCR) Center is an innovative, workshop‐based approach to research ethics education at the University of Pittsburgh. A flexibly scheduled program of workshops combines the benefits of traditional case–based discussion and in‐person instruction with greater accessibility and a broader disciplinary reach. Essential features of the program include a rotating schedule of independent workshops with separate registration, expert speakers, and a dedicated program director position. At an institutional level, this novel response to National Institutes of Health‐mandated training requirements increases access to a wide range of interactive RCR training programs and promotes interdisciplinary conversations on research ethics that involves investigators, trainees, and the research community at large.